2018
DOI: 10.1113/jp276372
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity has sex‐dependent effects on insulin, glucose and lipid metabolism and the liver transcriptome in young adult rat offspring

Abstract: Maternal obesity (MO) predisposes offspring (F1) to obesity, insulin resistance (IR) and non-alcoholic fatty liver disease (NAFLD). MO's effects on the F1 liver transcriptome are poorly understood. We used RNA-seq to determine the liver transcriptome of male and female F1 of MO and control-fed mothers. We hypothesized that MO-F1 are predisposed to sex-dependent adult liver dysfunction. Female Wistar rat mothers ate a control (C) or obesogenic (MO) diet from the time they were weaned through breeding at postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
92
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 69 publications
9
92
0
2
Order By: Relevance
“…Third, although we accounted for heterogeneity by using a random rather than a fixed effect model for meta‐analysis, variation between the studies was high. A recent study has suggested evidence of sex‐dependent differences in pathways related to CVD development . Our subgroup analyses based on offspring sex showed no differences in effects; however, not all studies could be included because of missing data on males and females separately.…”
Section: Discussionmentioning
confidence: 62%
“…Third, although we accounted for heterogeneity by using a random rather than a fixed effect model for meta‐analysis, variation between the studies was high. A recent study has suggested evidence of sex‐dependent differences in pathways related to CVD development . Our subgroup analyses based on offspring sex showed no differences in effects; however, not all studies could be included because of missing data on males and females separately.…”
Section: Discussionmentioning
confidence: 62%
“…We have previously reported that MO prior to and throughout pregnancy and lactation programme the offspring to the development of non‐alcoholic fatty liver disease in a sex‐dependent manner (Lomas‐Soria et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…PND 110 represents the young adult and was chosen to enable comparisons with our paper on RNASeq in programming, addressing mechanisms of MO programming of the liver at 110 days (Lomas‐Soria et al . ). PND 450 represents a mature adult and we have also published programming outcomes at this age (Rodriguez‐Gonzalez et al .…”
Section: Introductionmentioning
confidence: 97%
“…In a recent article by Lomas‐Soria et al . () in The Journal of Physiology , a cross‐sectional study was conducted to investigate the effects of MO on the development of NAFLD in young adult rat offspring. This study in particular was designed in part to address previous results showing programming by MO displays a bias between sexes whereby disease severity is often more pronounced in male than female offspring.…”
mentioning
confidence: 99%
“…To elucidate the underlying cause of these observed differences, Lomas‐Soria et al . () examined the effects of MO on female and male F1 rat livers independently by analysing liver metabolites, structure and transcriptome changes. This study was performed on F1 progeny from mothers who were fed with either a high‐fat or a control diet.…”
mentioning
confidence: 99%